Medical Ethics According to Avicenna’s Stance: A Synopsis: - Azmand, Sajad; Heydari, Mojtaba (Galen Medical Journal, 2017)
Medical ethics has been contemplated upon by practitioners since ancient times. Avicennaâ€™s notes on medical ethics are presented in the third chapter of the manuscript â€œFi Bayan al-hajat Ela al-Teb va al-Atteba va Vasayahomâ€ (meaning: â€œon needs to medicine and physicians and their recommendationsâ€) by Qutb al-Din Shiraziâ€™s (1236-1311 CE), one of the main commentators on Avicenna Canon of Medicine. Avicenna refers to several ethical subjects which can be expressed in three main domains: considering patient interests, communication skills, and adhering to the characteristics of professional excellence. Although there are similarities between the classical medical ethics recommendations and ethics recommendations raised by Avicenna, significant moral differences can be considered between the two views [GMJ.2017;6(4):261-7]DOI: 10.22086/gmj.v6i4.768